Implementation of sleep apnoea testing and treatment services into a cardiometabolic clinic for people living with severe mental illness: a prospective evaluation of a translational programme - Brendon J Yee; Ronald R Grunstein; Nathaniel S Marshall; Angela L D'Rozario; Paola Espinel; Garry Cho; Kathleen Smith; Henry W Ainge-Allen; Lachlan Stranks; Gislaine Gauthier; Timothy Lambert (BMJ Open)
Background Medical care for sleep-disordered breathing (SDB) in severe mental illness (SMI) is often ignored or poorly delivered. Here we describe an oximetry screening and management pathway for obstructive sleep apnoea (OSA) and assess the night-to-night reliability in a specialist cardiometabolic disease management clinic for patients with SMI.Objective The implementation and evaluation of a sleep service for patients living with SMI.Design Prospective evaluation of a translational programme.Setting A multidisciplinary outpatient clinic for patients with SMI.Methods The clinic was prospectively evaluated between May 2019 and December 2020. We used questionnaires and three nights of oximetry to screen patients for OSA. A project coordinator managed the testing-treatment pathway while liaising with health care providers. We also evaluated the agreement between two nights of oximetry.Results It is feasible to integrate sleep service into a cardiometabolic clinic for patients with SMI. Oximetry data were collected from 140/153 patients and 129/140 had at least adequate oximetry data for one night, and 107 (82%) had two nights. Oximetry indicated likely moderate-to-severe OSA in 33 patients and severe OSA in 22 patients. A total of 96/140 patients were referred to the SMI sleep clinic, and 40 (42%) recommended polysomnography (PSG) and 31 (78%) completed PSG. Of the 44 patients recommended continuous positive airway pressure (CPAP) therapy, 38 initiated CPAP and 20 (51.3%) demonstrated adherence (>4 hours 70% of nights over 30 days). Bland-Altman analysis of two nights of oxygen desaturation events greater than 4% per hour found a mean difference of −0.2 (95% CI −14.0 to 14.0). Misclassification of OSA severity was seen in 12 patients (18.7%).Conclusions Our recount shows the feasibility and effectiveness of implementing a sleep service in a cardiometabolic clinic for patients with SMI, and using oximetry is an effective diagnostic test of SDB. Having a dedicated project coordinator to oversee the clinical pathway avoids fragmentation of clinical services.